(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this study is to shed light on the linguistic landscape of social media in Saudi Arabia through an assessment of language usage, cultural expression, and societal changes. The present study investigates the linguistic inclinations of the online populace in Saudi Arabia, with a particular focus on the relative impact of Arabic and English and their respective spheres of influence. This study delves into the cultural manifestations that arise from the utilization of hashtags and memes, analysing their roles in social engagement and the establishment of social groups. The research utilizes a mixed-methods approach, encompassing both quantitative analysis of linguistic patterns and qualitative investigation of user-generated content. The methodologies employed in research encompass the use of questionnaires, face-to-face interviews, and analysis of social media content. Descriptive statistics, cross-tabulations, and chi-square tests are commonly employed in the analysis of quantitative data, whereas theme analysis is a widely used approach for examining qualitative data. The significance of this research lies in its novel contributions to the understanding of the unique dynamics of virtual discourse within the context of Saudi Arabian society. This study provides novel insights into the linguistic, cultural, and social expressions of individuals in Saudi Arabia through the medium of social media by comparing and contrasting its findings with those of prior research. The results contribute to the enhancement of communication strategies, the progress of social engagement, and the preservation of cultural resources in the digital realm.